CORRELATION BETWEEN NATURALIST INTELLIGENCE AND SCIENCE LITERACY - Sheila Agita Sari; Lilik Bintartik (Jurnal Ilmu Pendidikan Indonesia, 2026)
This study aims to examine the relationship between naturalist intelligence and science literacy of elementary school students. The method used is a quantitative approach with a correlational design. The research population amounted to 114 students in grades V and VI from two elementary schools in Blitar City, with saturated sampling techniques. Data were collected through Likert scale questionnaires and science literacy tests that have been tested for validity and reliability. The data analysis uses Spearman Rank correlation because the data is not normally distributed. The results of the study showed that most of the students were in the medium category. The correlation coefficient of 0.346 with p < 0.05 showed a significant positive relationship with moderate strength. These findings confirm the importance of environment-based learning to improve students' science literacy.